2008
DOI: 10.1136/ard.2008.093591
|View full text |Cite
|
Sign up to set email alerts
|

Does low-field dedicated extremity MRI (E-MRI) reliably detect bone erosions in rheumatoid arthritis? A comparison of two different E-MRI units and conventional radiography with high-resolution CT scanning

Abstract: With CT as the reference method for detecting erosions in RA hands, the Artoscan showed higher sensitivity than the MagneVu and CR. All imaging modalities had high specificities. The better performance of the Artoscan should be considered when selecting an imaging method in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 18 publications
1
21
1
3
Order By: Relevance
“…The superiority of MRI including E-MRI over conventional radiography has been confirmed in several studies [6,13]. Similarly, MRI erosion score was significantly higher in the established RA group compared to the early RA group, whereas there was no difference in sharp score between the two groups.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The superiority of MRI including E-MRI over conventional radiography has been confirmed in several studies [6,13]. Similarly, MRI erosion score was significantly higher in the established RA group compared to the early RA group, whereas there was no difference in sharp score between the two groups.…”
Section: Discussionmentioning
confidence: 73%
“…The MRI scoring system based on bone erosions, bone oedema and synovitis, developed by Outcome Measures in Rheumatoid Arthritis Clinical Trials (OMERACT) in 2002, known as the RA MRI scoring system (RAMRIS), has been accepted widely for use in RA trials [5]. Studies that evaluated the role of E-MRI in rheumatoid arthritis have shown that they provided information on bone erosions and synovitis comparable to that of high-field MRI [6,7]. Studies that evaluated the role of E-MRI in rheumatoid arthritis have shown that they provided information on bone erosions and synovitis comparable to that of high-field MRI [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional radiography is the best-validated imaging technique to assess bone damage so far, but there are limitations due to the two-dimensional character of radiographs 5. In consequence, MRI and CT gain importance for the assessment of bone erosions in RA 4 13. CT is often considered as the gold standard for detection of bone erosion as it combines the advantages of radiography for the assessment of bone structure with the strengths of tomographic techniques such as high degree of resolution and the three-dimensional character 3.…”
Section: Introductionmentioning
confidence: 99%
“…The Journal of on July 11, 2015 -Published by www.jrheum.org Downloaded from studies 9,10,11,12,13,14 , in which details on population characteristics and MRI techniques are described.…”
Section: Rheumatologymentioning
confidence: 99%